Reconstruction of Islamic Legal Thought in Thailand: Efforts to Realize Justice for the Muslim Minority - Da-Oh, Paison (International Journal of Sharia Studies, 2025)
Ideally, Islamic law in Thailand serves as a moral and juridical foundation for the Muslim community, particularly in the southern provinces of Pattani, Yala, and Narathiwat. In reality, however, the secular nature of the national legal system and the centralized state policy have restricted the implementation of Islamic law. As a result, Muslim minorities continue to experience structural injustice and social marginalization in accessing their religious and legal rights. This study aims to reconstruct Islamic legal thought in Thailand as an effort to achieve justice for Muslim minorities. The research employs a qualitative descriptive-analytical library approach, examining academic works, legal documents, and the thoughts of contemporary Muslim scholars in Thailand. The findings indicate that the application of maqasid al-shariah principles—such as al-‘adl (justice), musawah (equality), and maslahah (public interest)—can provide a foundation for a more inclusive and adaptive reform of Islamic law within a secular state context. Such reconstruction has the potential to strengthen Islamic institutions, promote just policies, and foster interreligious dialogue as a basis for social harmony in Thailand.